Legal Protection for Limited Liability Companies as Consumer Users of Virtual Office Services in Indonesia: Perlindungan Hukum Bagi Perseroan Terbatas Sebagai Konsumen Pengguna Jasa Virtual Office di Indonesia - Kemala, Ajeng Sukma (Indonesian Journal of Innovation Studies, 2023)
This study delves into the legal concerns surrounding limited liability companies utilizing virtual office services in Indonesia. Notably, the Consumer Protection Law of 1999 does not explicitly safeguard the consumer rights of virtual office service users. The research aims to scrutinize the legality of virtual office operations for such entities and propose a legal protection framework tailored to Indonesian law. The absence of explicit regulations poses uncertainties for limited firms using virtual offices, necessitating a comprehensive legal backing. Through a thorough examination, this study emphasizes the necessity of adequate legal measures to ensure the certainty and protection of limited companies engaging in virtual office usage. Highlights: Legal Ambiguity: The absence of explicit regulations challenges legal certainty for limited liability firms utilizing virtual office services. Consumer Rights Gap: The Consumer Protection Law of 1999 lacks provisions expressly addressing the rights of virtual office service users, especially limited liability companies. Need for Regulatory Clarity: This study emphasizes the urgency for a specific legal framework to safeguard and provide certainty for limited companies engaging in virtual office utilization within Indonesian legal parameters. Keywords: Virtual Office Services, Limited Liability Companies, Legal Protection, Consumer Rights, Indonesian Law